Key usability factors of service-oriented web sites for students: an empirical study - Nathan, Robert J.; Yeow, Paul H.P.; Murugesan, San (EMERALD GROUP PUBLISHING LIMITED, 2008)
Purpose - This paper aims to report on a web usability study and to identify and prioritise key web interface usability factors (WIUFs) for web sites of 36 student-related online services categorised into three groups: personal services, purchase services and study-related web sites.